ACC1 determines memory potential of individual CD4+ acid biosynthesis T cells by regulating de novo fatty. Issue 2 (February 2019) - Endo, Yusuke; Onodera, Atsushi; Obata-Ninomiya, Kazushige; Koyama-Nasu, Ryo; Asou, Hikari K.; Ito, Toshihiro
No abstract available